Proceedings of the 1993 International Symposium on Symbolic and Algebraic Computation - ISSAC '93 1993
DOI: 10.1145/164081.164139
|View full text |Cite
|
Sign up to set email alerts
|

Computing Gröbner bases in monoid and group rings

Abstract: FollowingBuchberger's approach to computing a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In the following we collect the necessary results generalizing the theory of prefix rewriting and prefix Gröbner bases for one-sided ideals of K[M ] developed in [20], [21], [22], and [27]. A Gröbner basis theory for the two-sided case can be introduced in a similar way.…”
Section: Remark 42 the Assumption Thatmentioning
confidence: 99%
See 3 more Smart Citations
“…In the following we collect the necessary results generalizing the theory of prefix rewriting and prefix Gröbner bases for one-sided ideals of K[M ] developed in [20], [21], [22], and [27]. A Gröbner basis theory for the two-sided case can be introduced in a similar way.…”
Section: Remark 42 the Assumption Thatmentioning
confidence: 99%
“…The generalized word problem (also called the submonoid membership problem) was discussed in [20]. It was shown that it leads to a subalgebra membership problem in K[M ].…”
Section: Proposition 52 (The Submodule Membership Problem)mentioning
confidence: 99%
See 2 more Smart Citations
“…This provides a link to the theory of term rewriting and the Zharkov/Blinkov method appears as an application of the pre x reduction/saturation technique of Madlener and Reinert (c.f. [MR93]) with a restricted saturation. The restricted saturation has its natural origin in the syzygy theory and heavily improves the termination behaviour in the particular case of Pommaret bases.…”
Section: Introductionmentioning
confidence: 99%